2020
DOI: 10.1002/humu.23977
|View full text |Cite
|
Sign up to set email alerts
|

Molecular insights into the mechanism of nonrecurrent F8 structural variants: Full breakpoint characterization and bioinformatics of DNA elements implicated in the upmost severe phenotype in hemophilia A

Abstract: Hemophilia A (HA) provides excellent models to analyze genotype–phenotype relationships and mutational mechanisms. NhF8ld's breakpoints were characterized using case‐specific DNA‐tags, direct‐ or inverse‐polymerase chain reaction amplification, and Sanger sequencing. DNA‐break's stimulators (n = 46), interspersed repeats, non‐B‐DNA, and secondary structures were analyzed around breakpoints versus null hypotheses (E‐values) based on computer simulations and base‐frequency probabilities. Nine of 18 (50%) severe‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 47 publications
(75 reference statements)
4
25
0
Order By: Relevance
“…In order to understand the molecular mechanisms leading to these Xq28 duplications, the characterization of breakpoints at the nucleotide level was required. Though many F8 deletion breakpoints have been sequenced, 25–27 sequencing duplication junctions has proved more challenging. LR‐PCR has been successfully used to characterize 10 F8 intragenic tandem duplications 17 .…”
Section: Discussionmentioning
confidence: 99%
“…In order to understand the molecular mechanisms leading to these Xq28 duplications, the characterization of breakpoints at the nucleotide level was required. Though many F8 deletion breakpoints have been sequenced, 25–27 sequencing duplication junctions has proved more challenging. LR‐PCR has been successfully used to characterize 10 F8 intragenic tandem duplications 17 .…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, we used several practical approaches, including SNP-array, WGS and customized PCRs. Followed by a bioinformatic approach, screening the surroundings of the SVs' breakpoints for the identification of DNA DSB stimulator motifs, which have been found statistically significantly more frequent at breakpoint junctions than expected by chance according to Abelleyro et al (2020) (Abelleyro et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, we want to highlight the important role that secondary structures must be exerting in the origin of SVs, given that we found them in 7/8 breakpoints. Its implication for DSB formation is suggested by the fact that if we randomly select 50pb throughout the genome it is very likely that they form secondary structures, but if we simulate random breakpoints and analyze 25bp at each side of it, the chances of finding secondary structures involving them are greatly reduced (Abelleyro et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human Gene Mutation Database (HGMD) has subdivided genomic deletions into microdeletions (1-20 bp) and gross deletions (>20 bp) (Stenson et al, 2020), but this distinction was originally made fairly arbitrarily for reasons of practical utility rather than for any cogent biological reason. Many studies (Carvalho & Lupski, 2016;Keute et al, 2020;Maranchie et al, 2004;Sahoo et al, 2006) have suggested the involvement of different mechanisms in the formation of microdeletions and gross deletions including nonhomologous end-joining (NHEJ), microhomology-mediated end-joining (MMEJ), non-allelic homologous recombination (NAHR), retrotransposon-mediated mechanisms, and replication-based errors including fork stalling and template switching (FoSTeS) and microhomology-mediated break-induced replication (MMBIR) (Abelleyro et al, 2020;Eckelmann et al, 2020;Bauters et al, 2008;Carvalho et al, 2009;Férec et al, 2006;Gadgil et al, 2020;Hu et al, 2019;Lee et al, 2007;Marey et al, 2016;Summerer et al, 2018;J. Vogt et al, 2014;Zhang et al, 2009Zhang et al, , 2010.…”
mentioning
confidence: 99%